PENGARUH MEDIA KARTU KATA BERGAMBAR TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS II SDN 09 KOTO BARU - Muhammad Subhan; Agus Saputra; Rahmatina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is based on problems in Indonesian language learning, where students lack interest in reading. The use of media in learning is also inappropriate. Through this problem, the aim of this research is to overcome the low initial reading ability. To overcome this, interesting and appropriate media is needed so that students can easily understand the material. Therefore, researchers will apply picture word card media as a learning medium. The type of research used was experimental, Pre Experimental Design. This research was carried out at SDN 09 Koto Baru class II in the even semester of the 2023/2024 academic year. The population in this study was all class II students consisting of one class with a total of 24 students. The development of the instrument used is a reading test in accordance with the initial reading assessment rubric. The data collection technique used was an initial test (pre-test) and a final test (post-test). The data analysis technique for this research uses the Normality Test and hypothesis testing. Based on the results of the Wilxocon test, the significance was 0.000<0.05, meaning that Ho was rejected and Ha was accepted. So it can be concluded that there is an influence of picture word card media on the beginning reading ability of class II students at SDN 09 Koto Baru.